GAMBARAN KEJADIAN DERMATITIS PADA TENAGA KERJA INDONESIA DI TEMPAT PENAMPUNGAN SEMENTARA DI KABUPATEN NUNUKAN - Arman Arman; Ari Udiyono; M. Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dermatitis is inflammation of the skin as a response against the influence of exogenous or endogenous factors that cause clinical disorders such asefloresensi polymorphic and complaints of itching. Data from Tarakan KKP working area Nunukan in 2015, the prevalence of dermatitis 53.2% of cases.This study aims to describe the incidence of dermatitis on migrant workers at the polling station in Nunukan. This type of research is descriptive with cross sectional design. The population in this study are all workers who are in the polling stations outpatient treatment Polyclinic Tarakan KKP working area Nunukan in september 2016 total 105 people with simple random sampling method sampling.Analysis of the data used areunivariate in the form distribution frequency table accompanied by narration.The results of this study found depiction of the incidence of dermatitis on migrant workers (64.8%) and, not dermatitis (35.2%). The incidence of dermatitis is dominated by age group ≥30 years (60.7%). The majority are those with history of skin diseases (84.2%) and had poor water quality (84.5%). The intensity of the shower bath is dominated by less than 2 times a day (85.3%), baths use rainwater (83.0%) and those who did not shower after work or sports (78.6%). the cleanliness of the clothes dominated by the change of clothes for less than 2 times a day (78.3%), did not iron clothes before use (65.4%), soak the clothes mixed with clothes friends (80.4%) and washes the clothes in a public toilet using rain water (65.3%)all of that included in the category of bad. It is expected to health workers to conduct socialization ofhygiene and health behaviorsin order to overcome the incidence of dermatitis andto the migrant workers, to always maintain personal hygiene and the cleanliness of clothes,as well as increasing proper bathing habits.